Tumors of the Sacrum : Diagnosis and Treatment of Benign and Malignant Tumors - Ruggieri, Pietro; Angelini, Andrea; Vanel, Daniel; Picci, Piero (Springer International Publishing : Imprint: Springer, 2017)
This book provides an up-to-date overview on the epidemiology, clinical presentation, and imaging characteristics of sacral tumors, discusses the available treatment options, and reports the published outcomes. The diagnostic roles of conventional radiology, CT, and MRI are thoroughly described and imaging appearances are compared with the histologic features. The coverage of therapeutic approaches includes chemotherapy, radiotherapy, radiosurgery, and surgery (partial or total sacrectomy and spinopelvic reconstruction). Special attention is paid to the specific anatomic constraints that make tumors in this region of the spine more difficult to manage effectively than those in the extremities and the mobile portions of the spine. All components of the sacrum can give rise to benign or malignant tumors, which pose significant diagnostic and therapeutic challenges. Although these tumors are often diagnosed at an advanced stage, good clinical outcomes may be achieved if an aggressive multidisciplinary approach is used. This book will be of value for a range of practitioners; it will assist in prompt diagnosis and help to overcome lack of familiarity with the required treatment strategies.